Development of Approaches to Ensuring Tax Security in the Region - Elena A. MURZINA; Marina S. SHEMYAKINA (Communications of International Proceedings, 2020)
The article reveals the tasks set before the formation of a tax control system in order to ensure the tax security of the region, the following: ensuring the established amounts of tax revenues to the budget, reducing tax arrears, increasing the effectiveness of tax control, improving the tax culture of taxpayers, implementing the principle of conscientious taxpayers, reducing the number of complaints and appeals of taxpayers. The author of this article considers it strategically important to increase the efficiency of tax control not through the application of tax sanctions, but through preliminary prevention of tax violations, informing taxpayers about potential risks, and building a comfortable business climate. The latter is especially relevant in the current epidemiological situation.
Keywords: Economic Security; Tax Security; Tax Control; Tax Security Risks; Tax Risk Management.